Characteristics of Endokarst Phenomenon on Mount Sewu in Gunung Kidul Regency, Yogyakarta Special Region - Muzani Jalaluddin; Aufeeazzahra Nurani Praninda Putri; Marisa Andriani; Sri Nurviana Mellenia; Yolanda Lourentina Br. Ginting (Universitas Pendidikan Indonesia, 2022)
Indonesia is a country that has a variety of interesting landforms. One of them is karst landforms. The distribution of karst areas in Indonesia is mostly composed of carbonate rocks, and a few karst areas consist of other rocks. Not all areas where carbonate rocks can be classified into karst areas. Because the formation of karst depends on climatic factors, orographic factors, and the lithology structure of the area. The phenomenon of endokarst is part of the karst landforms below the surface, which includes caves (stalactite and stalagmite formations), and underground river water flows. Caves and underground river water flow are characteristic of the endokarst of Mount Sewu. These caves and underground rivers have great potential for subsurface water resources (Santosa, 2015). The Mount Sewu is also a holokarst type karst. The phenomenon of the Mount Sewu endokarst is inseparable from the geological, geomorphological, hydrological, ecological, and cultural characteristics of the area. The existence of geological and geomorphological forms of karst on Mount Sewu brings many benefits, such as as a limestone mineral resource, a supplier of water resources, the Mount Sewu karst area as a geopark and ecotourism, and the existence of biodiversity. Therefore, because it is known that endokarsts have the potential for landforms in the form of caves and underground river water flows, it is very important to know and study karst landforms, especially regarding endokarsts, so that the karst landforms in Indonesia, especially in Mount Sewu, Gunung Kidul Regency. can be managed sustainably and utilized wisely.